Fractal characterisation of electrodispersed gold electrodes - Ocon, Pilar (1991)
The fractal dimension of the surface, Ds, of thin columnar gold electrodeposits (surface roughness factor 50–100) grown on gold wire cathodes by electroreducing hydrous gold oxide layers has been determined by measuring the diffusion controlled current of the Fe(CN)4−6/Fe(CN)3−6 reaction. The diffusion current (I) vs. time (t) relationships obeyed a Iαt−α dependence with Ds = 2α + 1. The initial Ds, value is 2.5 ± 0.1, and decreases to 2.3 ± 0.1 by keeping the deposit in contact with the electrolyte solution at 298 K due to the smoothing of the rough metal surface by surface diffusion.